Adjusting Pt Nanoparticle Size on SBA-15 by a Sol-Immobilisation Method Towards Naphthalene Hydrogenation - Liang, Yu; Zhao, Binbin; Tang, Qiong; Liu, Lei; Dong, Jinxiang (Catalysis letters, 2022)
Regularly dispersed Pt particles on SBA-15 supported catalysts were synthesized with a Pt loading of 5 w t% by a sol-immobilisation method, wherein various Pt particle sizes within 1–5 nm were finely controlled via the adjustment of the addition amount of polyvinyl alcohol (PVA). A high PVA/Pt ratio of the initial solution tended to generate small Pt particles on the SBA-15 support due to intense protection against Pt particle aggregation. In addition, the effect of Pt particle size on naphthalene hydrogenation was investigated in terms of catalytic performance. Compared with the performance of other catalysts with Pt particle sizes greater or less than 3.5 nm, Pt nanoparticles with sizes centered at 3.5 nm exhibited excellent catalytic performance towards decalin. This excellent catalytic performance was mainly attributed to a suitable ratio of the edge sites to flat sites on these Pt nanoparticles, benefitting the rapid adsorption of naphthalene and dissociation of hydrogen. Graphical Abstract The Pt/SBA-15 catalysts were prepared by sol-immobilisation method. The highest performance was attributed to the Pt-nanoparticles with suitable flat/edge sites ratio.